Photoresponse of 76Se below 9 MeV - Cooper, Nathan; Simon, Vanessa Véronique (Physical review. C, Nuclear physics, 2012)
The dipole strength distribution of 76Se has been investigated via photon scattering in the energy region below 9 MeV utilizing bremsstrahlung produced at the S-DALINAC facility at the TU Darmstadt. About 0.20(1)% of the classical E1 sum rule is exhausted by observed J=1 states of justifiably assumed negative parity. An extrapolation of the GDR below 9 MeV suggests that considerable strength may remain unobserved due to background, finite detector resolution, and fragmentation. The observed strength thus represents a lower limit. Candidates for the 2+1,ms state and a fragment of the 1+sc mixed-symmetry states are presented.